MROH7‐TTC4 read‐through lncRNA suppresses vascular endothelial cell apoptosis and is upregulated by inhibition of ANXA7 GTPase activity. (24th August 2019) - He, Xiaoying; Zhao, Xuan; Su, Le; Zhao, Baoxiang; Miao, Junying
Abstract : Apoptosis of vascular endothelial cells (VEC) is the main form of vascular injury that is closely linked to numerous cardiovascular diseases. Therefore, it is important to find new factors that can suppress VEC apoptosis. By using long noncoding RNA (lncRNA) microarray analysis, we found a new read‐through lncRNA, MROH7‐TTC4, which acted as an apoptosis inhibitor in VECs. Furthermore, by using the inhibitor (ABO) of annexin A7 (ANXA7) GTPase, we discovered that ANXA7 translocated into nucleus and interacted with 5′→3′ exoribonuclease (XRN2). The decreased XRN2 phosphorylation induced by ANXA7 GTPase activity inhibition, promoted MROH7‐TTC4 expression. Moreover, T‐cell intracellular antigen‐1 (TIA1), a binding protein of MROH7‐TTC4, processed it into MROH7 and TTC4 that could inhibit VEC apoptosis. Here, we conclude that inhibiting ANXA7 GTPase activity promotes the interaction of ANXA7 and XRN2 in nucleus, which regulates the read‐through transcription of MROH7‐TTC4, and TIA1 is responsible for the process of MROH7‐TTC4 that inhibits apoptosis through MROH7 and TTC4. Abstract : Schematic representation of the expression, regulation, and action mechanism of the newly identified long noncoding RNA MROH7‐TTC4, which inhibits apoptosis of vascular endothelial cells (VEC). Treatment with ABO decreases ANXA7 GTPase activity and then inhibits the phosphorylation of XRN2, a member of 5′‐to‐3′ exonucleases that contributes to the read‐through transcription of MROH7‐TTC4 . Downstream, the DNA/RNA‐binding protein TIA1 was shown to be responsible for MROH7‐TTC4 processing. MROH7 and TTC4 are then produced and are both able to inhibit VEC apoptosis.